2009
DOI: 10.1007/s00128-009-9760-2
|View full text |Cite
|
Sign up to set email alerts
|

Is the Cry1Ab Protein from Bacillus thuringiensis (Bt) Taken Up by Plants from Soils Previously Planted with Bt Corn and by Carrot from Hydroponic Culture?

Abstract: The uptake of the insecticidal Cry1Ab protein from Bacillus thuringiensis (Bt) by various crops from soils on which Bt corn had previously grown was determined. In 2005, the Cry1Ab protein was detected by Western blot in tissues (leaves plus stems) of basil, carrot, kale, lettuce, okra, parsnip, radish, snap bean, and soybean but not in tissues of beet and spinach and was estimated by enzyme-linked immunosorbent assay (ELISA) to be 0.05 +/- 0.003 ng g(-1) of fresh plant tissue in basil, 0.02 +/- 0.014 ng g(-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…Some of the results of this study [194] in which the Cry1Ab protein was apparently not taken up by plants from soils on which Bt corn had been previously grown, were in agreement with results of Saxena and Stotzky [82,195], who reported no uptake of the Cry1Ab protein, using the Western blot kit from EnviroLogix, by: (1) non-Bt corn, carrot, radish, and turnip grown in soil, in a plant-growth room, on which Bt corn had been grown or which had been amended with purified Cry1Ab protein or ground biomass of Bt corn; or (2) by non-Bt corn grown in sterile hydroponic culture in which Bt corn had previously been grown. However, some other results of this study were not in agreement with those of Saxena and Stotzky [82,195], as the Cry1Ab protein was detected in the tissues of various plants grown on soil previously planted to Bt corn by the Western blot kit from Agdia and by the ELISA kits from Agdia and Abraxis.…”
Section: Uptake Of Bt Cry Proteins By Plants In Soil and In Hydroponimentioning
confidence: 75%
See 3 more Smart Citations
“…Some of the results of this study [194] in which the Cry1Ab protein was apparently not taken up by plants from soils on which Bt corn had been previously grown, were in agreement with results of Saxena and Stotzky [82,195], who reported no uptake of the Cry1Ab protein, using the Western blot kit from EnviroLogix, by: (1) non-Bt corn, carrot, radish, and turnip grown in soil, in a plant-growth room, on which Bt corn had been grown or which had been amended with purified Cry1Ab protein or ground biomass of Bt corn; or (2) by non-Bt corn grown in sterile hydroponic culture in which Bt corn had previously been grown. However, some other results of this study were not in agreement with those of Saxena and Stotzky [82,195], as the Cry1Ab protein was detected in the tissues of various plants grown on soil previously planted to Bt corn by the Western blot kit from Agdia and by the ELISA kits from Agdia and Abraxis.…”
Section: Uptake Of Bt Cry Proteins By Plants In Soil and In Hydroponimentioning
confidence: 75%
“…Although this study indicated that some plant species grown in soils on which Bt corn had been grown take up the Cry1Ab protein, albeit in small amounts, more detailed studies with different methods and techniques are obviously needed to confirm this uptake [194]. If confirmed, the risks to the environment of such uptake will need to be evaluated.…”
Section: Uptake Of Bt Cry Proteins By Plants In Soil and In Hydroponimentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, Perry et al (2010) erroneously assume that the sensitivity of non-target butterflies Inachis io and Vanessa atalanta to MON 810 pollen is the same, which questions the validity of their mathematical model. Another example to show the importance of exact measurement of Bt toxin is Icoz, Andow, Zwahlen, and Stotzky (2009) that tried to determine the uptake of Bt toxins by various plants after growing Bt maize. They were not able to come to final conclusions and were questioning the accuracy and sensitivity of the available commercial test kits.…”
mentioning
confidence: 99%